2016
DOI: 10.1163/15685373-12342179
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Heritage Language on Ethnic Identity Formation and Literacy for u.s. Latino Children

Abstract: Studies show positive associations between ethnic identity, socio-emotional health and academic success. However, most work is carried out with adolescents and few have examined how young children develop an ethnic identity, particularly u.s. Latino children. The present study represents a first-pass investigation of children’s ethnic identity mechanisms and their relation to academic success. We carried out semi-structured interviews in Spanish with 25 Latino children (ages 5–12). Open-ended questions address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
1
27
0
4
Order By: Relevance
“…Given the growing immigrant and refugee populations across the world, parents often rely on their young children to translate and interpret for them in their new home country (Weisskirch, 2017b). While some children enjoy teaching and helping their parents learn a language, others report it as a negative laborious experience (Arredondo et al, 2016; Kam & Lazarevic, 2014). LB requires mature cognition including high levels of language fluency and social awareness—all of which are still developing in children and adolescents (Valdés, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing immigrant and refugee populations across the world, parents often rely on their young children to translate and interpret for them in their new home country (Weisskirch, 2017b). While some children enjoy teaching and helping their parents learn a language, others report it as a negative laborious experience (Arredondo et al, 2016; Kam & Lazarevic, 2014). LB requires mature cognition including high levels of language fluency and social awareness—all of which are still developing in children and adolescents (Valdés, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…LB requires mature cognition including high levels of language fluency and social awareness—all of which are still developing in children and adolescents (Valdés, 2003). LB is a multidimensional experience that provides children with positive bidirectional learning experiences (Arredondo et al, 2016; López, 2020) that support language proficiency (Buriel et al, 1998; Halgunseth, 2003; Hall & Sham, 2007), but may place brokers in stressful situations (Anguiano, 2018; Antonini, 2016; Katz, 2014). These experiences, while unique to bilingual immigrant children, are especially important to consider in terms of their long-term bilingual socio-emotional and cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, another important question for future research is how awareness of linguistic varieties in the heritage language may shape bilingual children's friendship formation with in‐group members as well as their ethnic identity development. In a recent study, Arredondo, Rosado, and Satterfield () show that children's proficiency in the heritage language supports ethnic identity formation by bolstering the formation of positive relationships and communication among members of their in‐group, including both children and their parents (see also Oh & Fuligni, ). Furthermore, being proficient in one's heritage language is associated with identifying closely with the ethnicity of one's family (e.g., Argentinian, Mexican, Puerto Rican) rather than using the American pan‐ethnic label to the ethnic group (Fuligni, Kiang, Witkow, & Baldelomar, ; Geerlings et al., ; Oh & Fuligni, ; see also Porter, Rheinschmidt‐Same, & Richeson, ; Rakic, Steffens, & Mummendey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Answers might reveal that the participant's family experienced racism for speaking Spanish, and that their parents subsequently discouraged them from speaking Spanish for fear of persecution (Zentella, 2009). Arredondo et al (2016) used a mixed-methods approach to examine the intricate relationship between Spanish abilities, attitudes, and ethnic identity development in Latinx children. Their work revealed that Spanish language proficiency was correlated to positive affect toward children's ethnic background, demonstrating the intrinsically important relationship between language and culture and their effects on language ability.…”
Section: Mixed Methods and Qualitative Researchmentioning
confidence: 99%